Pengembangan Community Based Tourism Sebagai Strategi Pemberdayaan Ekonomi Masyarakat - Danang Satrio; Choliq Sabana (LPPM Universitas Pekalongan, 2018)
In an effort to develop community-based tourism object Sand Kencana is a breakthrough for the development of tourism in the City of Pekalongan. Aside from being expected to be able to improve the socio-economic life of the surrounding communities, the development can also increase Regional Original Revenues. The aim of the research to be achieved is to know and analyze the potential and attractiveness of the Pasir Kencana Beach Tourism object and to know and analyze the community-based tourism development strategy in the Pasir Kencana Beach Tourism Object. The contribution in this research is that the concept of community-based tourism development is an effective step to make the tourism sector provide optimal economic benefits to the community because the community is directly involved in tourism management. In addition to providing economic benefits to the community, it will also provide education to the public on how to manage tourism objects, as well as how people understand, implement and maintain the sustainability of the Sapta Pesona concept at tourist sites.